2011
DOI: 10.1104/pp.111.184564
|View full text |Cite
|
Sign up to set email alerts
|

The Presequence of Arabidopsis Serine Hydroxymethyltransferase SHM2 Selectively Prevents Import into Mesophyll Mitochondria    

Abstract: Serine hydroxymethyltransferases (SHMs) are important enzymes of cellular one-carbon metabolism and are essential for the photorespiratory glycine-into-serine conversion in leaf mesophyll mitochondria. In Arabidopsis (Arabidopsis thaliana), SHM1 has been identified as the photorespiratory isozyme, but little is known about the very similar SHM2. Although the mitochondrial location of SHM2 can be predicted, some data suggest that this particular isozyme could be inactive or not targeted into mitochondria. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 41 publications
2
56
0
Order By: Relevance
“…Taken together, our results provide additional evidence that SHMT activity and photorespiration play a critical role in plant salt tolerance and that UBP16 plays a role in this regulation, in part, by modulating SHM1activity. SHM proteins mainly function in mitochondria and mediate ROS generation, which is important in both plant abiotic and biotic stress responses (McClung et al, 2000;Bauwe and Kolukisaoglu, 2003;Moreno et al, 2005;Jamai et al, 2009;Engel et al, 2011). Both ubp16 and shm1 mutants accumulated more ROS and a cell death signal (Cytochrome C in the cytoplasm) under salt stress along with more salt-induced cell death than Col-0, suggesting that one explanation for the salt sensitivity of the ubp16 mutant could be ROS accumulation-induced cell death through the regulation of SHM1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, our results provide additional evidence that SHMT activity and photorespiration play a critical role in plant salt tolerance and that UBP16 plays a role in this regulation, in part, by modulating SHM1activity. SHM proteins mainly function in mitochondria and mediate ROS generation, which is important in both plant abiotic and biotic stress responses (McClung et al, 2000;Bauwe and Kolukisaoglu, 2003;Moreno et al, 2005;Jamai et al, 2009;Engel et al, 2011). Both ubp16 and shm1 mutants accumulated more ROS and a cell death signal (Cytochrome C in the cytoplasm) under salt stress along with more salt-induced cell death than Col-0, suggesting that one explanation for the salt sensitivity of the ubp16 mutant could be ROS accumulation-induced cell death through the regulation of SHM1.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a mutation in SERINE HYDROXYMETHYLTRANSFERASE1 (shm1-2, a weak allele) leads to overaccumulation of ROS and that the mutant is more sensitive to salt stress and pathogens than is the wild type (Moreno et al, 2005). The Arabidopsis genome encodes seven SHM genes, and few of these gene products have been shown to function in mitochondria (McClung et al, 2000;Bauwe and Kolukisaoglu, 2003;Jamai et al, 2009;Engel et al, 2011). SHM1 is the major SERINE HYDROXYMETHYLTRANSFERASE (SHMT) isozyme in Arabidopsis leaves (Somerville and Ogren, 1981;McClung et al, 2000); the shm1-1 mutant was the first photorespiratory mutant identified in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple SHMT isoforms in higher plants and these genes are active in different compartments [22]. For example, in Arabidopsis there are two active isoforms targeted to the mitochondria, and they work together to handle an increased workload in non-photosynthetic tissues during times of increased demand for C1 metabolism [23]. Glycine decarboxylase (GDC) is an important regulatory enzyme for photosynthesis and photorespiration [24] as well as being involved in C1 metabolism by donating a carbon group from glycine to the pathway.…”
Section: Methionine Biosynthesismentioning
confidence: 99%
“…Seven SHMT genes have been found in Arabidopsis , two of which encode similar mitochondrial isoforms, SHM1 ( At4g37930 ) and SHM2 ( At5g26780 ) (Somerville et al 1981; Zhang et al ; Engel et al ). SHM1 was reported to play a critical role in controlling cell damage caused by abiotic stress, whereas its mutant shm1‐1 has the conditional lethal photorespiratory phenotype (Moreno et al ; Voll et al ).…”
Section: Introductionmentioning
confidence: 99%
“…SHM1 was reported to play a critical role in controlling cell damage caused by abiotic stress, whereas its mutant shm1‐1 has the conditional lethal photorespiratory phenotype (Moreno et al ; Voll et al ). Recently, SHM1 and SHM2 were shown to operate in a redundant manner in one carbon metabolism of non‐photorespiring cells with high demand of one carbon units (Engel et al ).…”
Section: Introductionmentioning
confidence: 99%